Prescribing Profile among Pregnancy in the Outpatient Pharmacy Installation of Bokor Hospital, Malang : Prescribing Profile of Pregnant Women at the Outpatient Pharmacy Installation of Bokor Hospital Malang Regency - Endang Susilowati; Dini Mei Arisa (Akademi Farmasi Surabaya, 2022)
Drug therapy in pregnant women is important because it can cross the placental blood barrier so that it has a negative effect on fetal development. This study aims to determine the profile of drug prescription in pregnant women including drug therapy class, drug name, drug category based on fetal safety. This study aims to determine the profile of drug prescribing in pregnant women including drug therapy class, type of drug and drug category based on safety for the fetus. The study used retrospective data in the form of 100 prescription sheets at the Outpatient Pharmacy Installation of Bokor Hospital, Malang Regency, the period July-September 2021. The results showed that there were 14 different classes of drug therapy prescribed to pregnant women. The number of vitamin and mineral prescription cases was 116 prescriptions (54%) with 100 prescriptions (46%) consisting of 13 drug therapy classes. Five percentages of prescriptions were vitamin-mineral 54%, analgesic 18.5%, tocolytic 5.1%. 4.6% and antiemetics 4.2%. Four types of drugs were prescribed from each therapeutic class, namely mefenamic acid (analgesic), Isoxsuprine HCl (tocolytic), Ondansetron (antiemetic) and amoxicillin (antibiotic). Based on drugs to the fetus, drugs prescribed to pregnant women are included in categories A, B, C and D. In conclusion, the most prescriptions for pregnant women are vitamin and mineral supplements, analgesics, and tocolytic drugs.